The Equilibrium Consequences of Indexing - Bond, Philip; García, Diego (Review of Financial Studies, 2021)
Abstract We develop a benchmark model to study the equilibrium consequences of indexing in a standard rational expectations setting. Individuals incur costs to participate in financial markets, and these costs are lower for individuals who restrict themselves to indexing. A decline in indexing costs directly increases the prevalence of indexing, thereby reducing the price efficiency of the index and augmenting relative price efficiency. In equilibrium, these changes in price efficiency in turn further increase indexing, and raise the welfare of uninformed traders. For well-informed traders, the share of trading gains stemming from market timing increases relative to stock selection trades.